POTENSI MINYAK ATSIRI DARI DAUN TUMBUHAN SAMBUANG (Etlingera elatior) SEBAGAI SENYAWA ANTIBAKTERI DAN ANTIOKSIDAN - M. Fadly; Suryati Suryati; Farid Al-Huzaini; Nadila Arrahim (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2021)
Sambuang (Etlingera elatior) is a member of the Zingiberaceae family which is widely distributed in Indonesia. Traditionally, sambuang is used for cooking spices and to cure various diseases, namely diseases of the ears, stomach, skin wounds, and stomach pain due to poisoning. In this study, essential oils were isolated from sambuang leaves and antibacterial and antioxidant activities were also determined. Isolation of essential oil was carried out by steam distillation and the chemical content of the isolated essential oil was analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). It is known to contain 98 chemical compounds, with the main ingredients being a-Pinene (19.39%), Gadoleyl Alcohol (7.37), Myristoleyl Alcohol (7.16%), Palmitoleyl Alcohol (5.87%), Sabinene (5 ,48%). The results of the antibacterial activity of essential oils using the disc diffusion method showed strong activity against Escherichia coli, Salmonella typhi (50% concentration) and Staphylococcus aureus (70% concentration) with inhibition zones of 13.6 mm, 12 mm, respectively. and 11 mm. The results of the antioxidant activity test using the DPPH method (1,1-diphenyl-2-picrylhydrazyl) showed that the essential oil of sambuang leaf essential oil was not effective as an antioxidant because it was very weak with an IC50 value of 6939.18 g/mL.